Mechanisms of Post-Pancreatitis Diabetes Mellitus and Cystic Fibrosis-Related Diabetes: A Review of Preclinical Studies - Gál, Eleonóra; Dolenšek, Jurij; Stožer, Andraž; Czakó, László; Ébert, Attila; Venglovecz, Viktória (Frontiers in Endocrinology, 2021)
Anatomical proximity and functional correlations between the exocrine and endocrine pancreas warrant reciprocal effects between the two parts. Inflammatory diseases of the exocrine pancreas, such as acute or chronic pancreatitis, or the presence of cystic fibrosis disrupt endocrine function, resulting in diabetes of the exocrine pancreas. Although novel mechanisms are being increasingly identified, the intra- and intercellular pathways regulating exocrine–endocrine interactions are still not fully understood, making the development of new and more effective therapies difficult. Therefore, this review sought to accumulate current knowledge regarding the pathogenesis of diabetes in acute and chronic pancreatitis, as well as cystic fibrosis.